IMAJI PADA ALBUM STILL DREAMING OLEH TOMORROW X TOGETHER : SEBUAH KAJIAN STILISTIKA - Ira Datul Aini; Hendri Zalman (Universitas Negeri Padang, 2022)
This research describes the imagery in the lyrics of the song on the Album Still Dreaming by Tomorrow x Together: a stylistic study. This type of research is qualitative with descriptive method. The purpose of this research is to find out what types of images are contained in the album Still Dreaming by Tomorrow x Together and what are the words and phrases in the lyrics of the song. The data of this research are sentences that contain phrases and words of images as well as the types of images in the song lyrics on the album Still Dreaming by Tomorrow x Together. The data source in this research consisted of 10 songs containing the album Still Dreaming by Tomorrow x Together. The total data findings are 22 data, consisting of 14 visual images, 4 auditory images, 2 olfactory images, one tactile image and 1 Gustatory imagery.